Promotional effect of Ce on catalytic performance for the glycerol hydrogenolysis over Ni–Ce/RSAC catalyst. (2022) - Subba Rao, K.; Palle, Kishor; Naga Gayatri, S.; Kumar, Narendra Phani; Angajala, Kishore Kumar; Shanthi, V.
Abstract: Activated carbons are prepared from Rice Straw used for metal impregnation. Glycerol hydrogenolysis in aqueous medium was carried out on Ni–Ce/RSAC catalyst. In contrast by other metals, such as Cu, Sn, Zn, Al, Fe & Co, Ce demonstrated a markedly enhanced catalytic performance. For example, 80.5% conversion of glycerol could be accomplished at 300 °C under 5 MPa of H2 with 6 h. XRD, H2 -TPR, TEM, NH3 -TPD, N2 physisorption, and characterization were performed on the Ni–Ce/RSAC catalyst. It was found that adding Ce to Ni/RSAC catalyst highly affected reduction behavior.